Stuttering: the nature of the speech disruptions—a multimodal study of articulation and phonation - Alm, Per A.; Brösemyr, Therése; Grinde, Sofie; Johansson, Sara; Karlsson, Jessica; Nordgren, Gustav; Olsson, Ronja; Rocksten, Frida; Sandsten, Maria; Sör, Ingrid; White, Denise (Frontiers in Human Neuroscience, 2025)
Stuttering is a disorder characterized by transient disruptions in speech motor production. This article is focused on the characteristics of stuttering and the immediate vocal tract mechanisms resulting in stuttered speech disruptions. A range of observations from an initial series of studies on the motor characteristics of stuttering events in adults is presented, combined with a narrative review of published data regarding objective and subjective aspects of instances of stuttering. The aims of the empirical studies were to develop methods for data collection and analysis, as well as collecting and analyzing initial data. The analysis was exploratory and qualitative, focusing on physiological data from individual stuttering events in order to understand their underlying dynamics and mechanisms. As a frame of reference, the motor characteristics and subjective experiences of stuttering were compared with the characteristics of known movement disorders, such as dystonia, motor blocks (e.g., freezing of gait), and tremor. The results show that stuttering events can include both negative and positive motor signs. It is proposed that stuttered disruptions can arise both as a result of insufficient muscular activation and as a result of interfering dysfunctional muscular activity. It is further suggested that the characteristics of stuttering to a very high degree correspond to motor block symptoms, indicating a transient inability to execute the next motor program in the speech sequence. Elements of dystonia may account for some symptoms. Volitional attempts to break fixed postures may increase the muscular tension and result in tremor, similar to dystonic tremor. The severity of the tremor is strongly correlated with the severity of physical concomitants. Tremor may be silent, as well as resulting in rapid audible repetitions if the vocal tract is opened and closed at the tremor frequency. Silent periods in stuttering can result from total closure of the airway at the level of the larynx, the tongue, or the lips. However, silent periods can also result from excessive opening of the vocal folds, leading to silent airflow and an inability to phonate. It is proposed that the motor blocks stem from transient decoupling between cortical and basal ganglia networks.